Examining Discourses on Integration of Philosophy and Religion (Analysis from Al-Ghazali to Al-Attas) - Patimah Patimah; Hamid Fahmy Zarkasyi; Saim Kayadibi (Tasfiyah: Jurnal Pemikiran Islam, 2022)
The discourse on the integration of philosophy and religion is important because they are an essential aspect of society. This paper first tries to understand philosophy and religion, their terminologies and definitions, and theories in relating philosophy and religion. The main section of this article examines Muslim thinkers' views on philosophy and religion and frames them in Barbour’s theory of integration. While it emphasizes Ghazāli's view on Reason and Revelation and Ibn Sīnā's view on Reason and Revelation, it also discusses the thoughts of Al-Farabi, Ibn Taymiyyah, Sir Muhammad Iqbal, and Syed Muhammad Naquib al-Attas. There are similarities and differences in Muslim scholars' views on the integration of philosophy and religion. Regardless of their differences, we found that all of them are still in Barbour’s definition of Integration, not Dialogue, independence, or even Conflict.